Distal supports, capabilities, and growth‐focused recovery: A comparison of Housing First and the staircase continuum of care - Greenwood, Ronni Michelle (2024)
Adults who have substantial histories of homelessness and complex support needs may feel ambivalent about integrating into their communities and find it difficult to do so. Being familiar to and recognized by others as a resident in a neighborhood or community are sources of “distal support” that provide individuals with feelings of belonging to their community and are important to recovery from homelessness. We hypothesized that individuals engaged with Housing First (HF) programs would report more distal support than individuals engaged with traditional homeless services (treatment as usual, TAU), and that distal support would predict more community integration, growth‐related recovery, and achieved capabilities. We analyzed data collected from homeless services users (n = 445) engaged with either HF or TAU in eight European countries. Measures included achieved capabilities, growth‐focused recovery, distal supports, and community integration. Serial mediation analyses confirmed our hypothesis that the effects of HF on growth‐related recovery and achieved capabilities are indirect, mediated by distal supports and community integration. Findings are discussed in relation to the importance of modeling the effects of HF on social and psychological outcomes as indirect and identifying important mediators that translate the effects of HF components on social and psychological outcomes. We also note the importance of case management activities that encourage clients to develop and sustain distal supports with others who live and work in their neighborhoods.